EQUIVALENT SURVIVAL OUTCOMES ACROSS DIFFERENT MANAGEMENT STRATEGIES IN PARTIAL SMALL BOWEL OBSTRUCTION AT DR. KARIADI HOSPITAL, SEMARANG IN JANUARY - DECEMBER 2024 - Gunadi, Ezra Endria; Mughni, Abdul (Folia Medica Indonesiana, 2025)
Small bowel obstruction (SBO) is[30pc]AU: Please provide the publication history dates. a common clinical condition in general surgery, contributing to approximately 12% of surgical admissions globally. With over 300,000 operations performed annually, timely and appropriate management is crucial for reducing morbidity and mortality. Although operative management remains standard in many cases, non-operative strategies are increasingly utilized. However, comparative evidence on survival outcomes, particularly from developing countries, remains limited. To improve health outcomes, this study aimed to evaluate the survival outcomes of operative and non-operative management strategies for partial SBO at a tertiary referral hospital. A retrospective analytical cross-sectional study was conducted from January to April 2025, using total sampling of medical records from patients with SBO treated at Dr. Kariadi General Hospital, Semarang, between January and December 2024. Inclusion criteria were adults (≥18 years) with mechanical SBO. Patients with non-mechanical obstruction, incomplete records, or prior treatment elsewhere were excluded. Data were analyzed using SPSS v26.0 with univariate and bivariate analyses. Statistical significance was set at p<0.05. A total of 167 patients were included (mean age 50.60 ± 14.94 years; 52.1% female). Operative management was performed in 67.1% of cases, with a 9.6% conversion rate from non-operative methods. The average hospital stay was 11.46 ± 8.36 days. Overall survival was 65.9%, with 67.9% in the operative group and 61.8% in the non-operative group (p = 0.489). Both management strategies resulted in clinical improvement, with no significant difference in survival outcomes.